Population Structure And Habitat Stratification Of Daily Activity Of Monkey Long Tail (M. Fascicularis) Which Located At Hutan Lindung Iboih Kota Sabang - Frida Fadwa; Abdullah Abdullah; M Ali Sarong (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
This research was done through the observation of population structure and habitat stratification of daily activity of Monkey long tail (M. fascicularis) which located at hutan lindung Iboih Kota Sabang. This research is descriptive with quantitative approach. This research was held in hutan lindung Iboih, Sabang district on June until July 2016.The collective data on population structure observation and grouping size of M. fascicularis by using concentration count method and for observing daily activity of M. fascicularis , scan sampling method was used. Based on the research shown that (1) Population structure of M. fascicularis on the 1st location was ranged in beween 11-12 individual. On the 2nd location was ranged in between 20-25 individual and on the 3rd location was ranged in between 10-15 individual. (2) Habitat stratification which used by M. fascicularis is more dominant by using E stratum (0 meter). Dominant activity is dynamic activity with the number of percentage is about 37,05% comparing with other activities. On the other hand the reproduction activity is more frequent doing in the altitude between 1-5 meter (D stratum) with the percentage is about 1,40% comparing with E stratum (0 meter) which only has the percentage about 0,17%. (3) The most frequent behavior which was done by the group of M. fascicularis is the behavior of moving which has the percentage about 39,50% comparing with other activities. The conclusion of this research is the population structure of M. fascicularis will form the inverted pyramid, because the mature individual is more dominant comparing with the young individual. These facts cause the age structure of long tail-macaque categorize in the regressive population.